Pengenalan Makna Gerak dan Nilai Filosofis Tari Tanggai bagi Siswa SMK Manggala Palembang - Heryati Heryati; Yusinta Tia Rusdiana; Dewi Setyawati; Yoga Pratma; Brata Brata (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aimed to introduce the meanings of movements and philosophical values of the Tanggai Dance to students of SMK Manggala Palembang as an effort to preserve the local culture of South Sumatra. Tanggai Dance is one of the traditional dances that contains aesthetic, ethical, and symbolic values representing respect and hospitality of the Palembang community. The implementation methods included counseling sessions, dance movement demonstrations, interactive discussions, and direct practice. The participants consisted of 30 students who actively attended all activity sessions. Data collection techniques were carried out through observation, interviews, documentation, and questionnaires distributed before and after the activity. The results showed an increase in students’ understanding of the meanings of movements and philosophical values of the Tanggai Dance. Before the activity, the students’ level of understanding was categorized as low with an average percentage of 45%, while after the activity it increased to 85% in the good category. In addition, students demonstrated high enthusiasm and interest in preserving local culture. This activity had a positive impact in fostering the younger generation’s appreciation of local cultural arts and strengthening regional cultural identity within the school environment.